Palaeohispanic epigraphy from El Pueyo (Belchite, Zaragoza). A new Celtiberian inscription in stone (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The aim of the paper is to present a new Celtiberian inscription recently found at the site of El Pueyo (Belchite, Zaragoza). This new inscription, along with the one found in 2013, shows the epigraphic importance of the site and helps to enhance the knowledge of this type of Celtiberian epigraphy.
Keywords: Epigraphy